Effect of walking meditation on perceived stress and mental well-being in oncology health-care professionals: A randomized controlled trial - Anjali Mangesh Joshi; Suchitra Ajay Mehta; Santoshi Raju Wadhwani (Yoga-Mimamsa)
Introduction: Occupational stress and burnout affect the psychological well-being of oncology health-care professionals (OHCPs). This study evaluated the effects of 6 weeks of movement-based walking meditation (WM) intervention on perceived stress (PS) and mental well-being (MWB) in OHCPs working at a tertiary care super specialty oncology hospital in central India. Materials and Methods: n = 62 OHCPs were randomly assigned to the intervention (n = 32) or the control group (n = 30). The PS Scale and Warwick-Edinburgh Mental Well-being Scale were used for assessments at the baseline and after 6 weeks. The intervention group practiced 20 min of WM daily, with moment-to-moment awareness of the physical sensations, thoughts, and emotions during walking. The control group did not receive any intervention. Results: n = 53 participants (n = 25 in the intervention and n = 28 in the control group) were included in the analysis. At the end of 6 weeks, the control group showed a significant increase in PS (p < 0.001, Cohen’s d = 3.38) and a decline in MWB (p < 0.001, Cohen’s d = 6.46). In the intervention group, a comparison of pre–post scores demonstrated a significant reduction in PS (p < 0.001, Cohen’s d = 3.23) and improvement in MWB (p < 0.001, Cohen’s d = 5.26). The group comparison of postscores indicated a significant reduction in PS (p < 0.001, Cohen’s d = 4.43) and improvement in MWB (p < 0.001, Cohen’s d = 8.41) in the intervention group as compared to the control group. No unanticipated adverse events were observed. Conclusion: The results highlight the efficacy of a life-based WM intervention to address the mental health challenges of OHCPs. Further validation is required to draw definitive conclusions.